Pengaruh Penambahan Jamur Pelapuk Putih (White Rot Fungi) pada Proses Pengomposan Tandan Kosong Kelapa Sawit - Nasrul, Nasrul; Maimun, Teuku (Jurnal Rekayasa Kimia & Lingkungan, 2010)
Composting is nowadays a general treatment method for agriculture waste such as empty fruit bunch. This research article reported the composting process of the empty fruit bunches. The effect of addition of white rot fungi (Phanerochaete Chrysosporium) as an activator on composting product was studied. Experiment results indicated that white rot fungi is a good activator to improve degradation process of the empty fruit bunch become an organic fertilizer. White rot fungi has capable to increase composting period become shorter in compare with original composting without addition of white rot fungi. The organic fertilizer product as regulation issued by the Standar Nasional Indonesia (NSI) can be achieved in duration of 3 months, while for original process without addition of white rot fungi longer degradation time is necessary.Keyword: Composting, empty fruit bunch, white rot fungi